2008
DOI: 10.3989/scimar.2008.72n3477
|View full text |Cite
|
Sign up to set email alerts
|

Descripción del gran ecosistema marino del noreste de Brasil usando un modelo trófico

Abstract: The objective of this study was to describe the marine ecosystem off northeastern Brazil. A trophic model was constructed for the 1970s using Ecopath with Ecosim. The impact of most of the forty-one functional groups was modest, probably due to the highly reticulated diet matrix. However, seagrass and macroalgae exerted a strong positive impact on manatee and herbivorous reef fishes, respectively. A high negative impact of omnivorous reef fishes on spiny lobsters and of sharks on swordfish was observed. Spiny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This subprovince extends from eastern tip of the mouth of the southern channel of the Amazon estuary to Parnaíba coast (Delta do Parnaíba; 2 • 43 S), state of Piauí. (iii) The Northeastern semiarid (NS) subprovince (2-5 • S) comprises a coastline of 720 km dominated by mobile dune fields propelled by south-easterly and easterly trade winds, which reach speeds of over 15 m/s (Freire et al, 2008). Low riverine input and clear and salty waters (annual salinity range 32-42) are characteristics of this region, in addition to relatively reduced mangrove forest cover along the coastline in comparison with the AE and NM subprovinces.…”
Section: Study Areamentioning
confidence: 99%
“…This subprovince extends from eastern tip of the mouth of the southern channel of the Amazon estuary to Parnaíba coast (Delta do Parnaíba; 2 • 43 S), state of Piauí. (iii) The Northeastern semiarid (NS) subprovince (2-5 • S) comprises a coastline of 720 km dominated by mobile dune fields propelled by south-easterly and easterly trade winds, which reach speeds of over 15 m/s (Freire et al, 2008). Low riverine input and clear and salty waters (annual salinity range 32-42) are characteristics of this region, in addition to relatively reduced mangrove forest cover along the coastline in comparison with the AE and NM subprovinces.…”
Section: Study Areamentioning
confidence: 99%
“…Diet compositions in the networks were derived from an isotope study of the region [55,56], and from literature (S3 Table). The fate of biomass not consumed in the systems was assigned to the various [non-living] abiotic groups (S2 Table).…”
Section: Methodsmentioning
confidence: 99%
“…Food-web models suggest that large sharks are among the most strongly interacting species [55], and that their overfishing may have contributed to the degradation of the coral ecosystems in the Caribbean [56]. A 'removal' computer simulation conducted for the reef ecosystem of Floreana Island in the Galápagos Islands found that sharks were at the top of the trophic scale and that their loss caused a four-level trophic cascade [57].…”
Section: The Ecological Consequencesmentioning
confidence: 99%